IP security - Singh, Saroj (International research journal of management, IT and social sciences, 2016)
IP is stands for Internet Protocol. IP security is a set service which secures the documents by the unauthorized entity. IP Sec covers the three areas of functionality that is authentication, confidentiality, and key management. IP Sec encrypts and authenticates all the data traffic at the IP level security. The IP level security or firewall administrator, we got basically the same concerns (as plumber) the size of the pipe the contents of the pipe, making sure the correct traffic is in the correct pipes and keeping the pipes from splitting and leaking all over the places of course like plumbers. When the pipes do leak: we are the ones responsible for cleaning up the mess and we are the ones who come up smelling awful. Firewall is a device that is used to provide protection to a system from network-based security threats. Firewall uses service, behavior, user and direction control techniques.